Refining the safety assessment of newly expressed proteins in GMOs - Sánchez-Brunete, Elena; Ferrari, Arianna; Moreno, F. Javier; Goumperis, Tilemachos; Ardizzone, Michele; Schoonjans, Reinhilde; Dewhurst, Ian; Dimitrov, Ivan; Epstein, Michelle M.; Koning, Frits; Hogeveen, Kevin; Fernández-Dumont, Antonio (Frontiers in Toxicology, 2025)
The European Food Safety Authority (EFSA) carries out safety assessments of newly expressed proteins (NEPs) in genetically modified organisms (GMOs). Here, toxicity and allergenicity assessments are the cornerstone of NEP evaluation, ensuring that any potential health hazards are rigorously identified and characterised. Recent examples of EFSA’s NEP safety assessments illustrate how novel methodologies, alongside established ones reconsidered from new perspectives, guide case-by-case decisions. These advances provide an opportunity to improve the robustness, proportionality, and scientific credibility of risk assessments. Moreover, it may alleviate the need for in vivo animal testing. Building on this development, EFSA aims to integrate new approach methodologies (NAMs) into risk assessment to provide a scientific basis for waiving in vivo testing, aligning its approach with the 3Rs principles (Replacement, Reduction, Refinement) and the European Commission’s roadmap for phasing out animal testing. Overall, this shift reflects a broader transformation in EFSA’s safety assessment of NEPs, characterised by openness to innovation, optimisation of existing methods, and ensuring preparedness for future risk assessment needs. The ultimate goal is to ensure the highest level of protection for human and animal health, while embracing scientific progress.